Adaptive disembodiment: towards an enactivist theory of body schematic sensorimotor autonomy - White, Halie Elizabeth, author; MacKenzie, Matthew, advisor; Rice, Collin, committee member; Snodgrass, Jeffrey, committee member (Colorado State University. Libraries, 2023)
The enactivist approach to embodied cognition relies on a non-reductive biological naturalism that is recursive at higher levels of complexity in living systems. In addressing an account of cognition, I will consider Xabier Barandiaran's objection that biological autonomy properly sets biological norms but under-specifies sensorimotor normativity. Barandiaran suggests the implementation of pluralist autonomy to the meta-pattern of organization in the enactivist agent that becomes recapitulated. By forming an account of sensorimotor autonomy, we can then specify normativity at the sensorimotor (cognitive) level. In consideration of this issue, I will propose the body schema functions to provide sensorimotor autonomy to the embodied subject through motor stability and thus functions to specify normativity at the sensorimotor level. This then allows for what enactivists term 'sense-making' in terms of enacting affordance structures. The position I take within the enactivist frame is thus a pluralist autonomist view on cognition. I go on to consider how this view bears on cognitive case studies often addressed in body schema literature. Drawing primarily from the work of Shaun Gallagher, body schema interacts with and develops body image through primary and secondary intersubjective capacities. I argue that body image is intersubjectively constructed through joint attention, thus invoking considerations of one's social milieu. This consideration shifts the discussion to address how the pluralist autonomist enactivist, through body schema and body image interaction, can account for alterations of the body schema due to distortions in one's body image that result from oppression. This pluralist autonomist enactivist theory provides three benefits for understanding these alterations: (1) enactivism begins with a fundamental postulate that individuals are embedded in a world; (2) in distinguishing between different levels of autonomy, we can thus discuss different forms of normative interaction with the environment; (3) and finally, with differentiated forms of normativity, we can thus differentiate and track different modes of adaptation an embodied subject can take when faced with various sorts of perturbations. I argue that disembodiment can be seen as an adaptation of the body schema in relation to hostile environments where stigma targets the body image. This hostile environment does not allow one's comfortable and normative navigation of the world due to the hypervisibility of the body. I explore this case of adaptive disembodiment through fatphobia and public weight stigma.
Keywords: body schema; enactivism; phenomenology; disembodiment; body image; fatphobia